COVID-19 orphans-Global patterns associated with the hidden pandemic. - Callum Lowe; Leli Rachmawati; Alice Richardson; Matthew Kelly (Public Library of Science (PLoS), 2022)
Whilst the COVID-19 pandemic has caused significant mortality across the globe, many children have been orphaned due to the loss of their parents. Using the framework of an ecological analysis, we used estimates of total maternal/paternal orphans using an online COVID-19 orphanhood calculator to estimate the total orphans per COVID-19 death for 139 countries. Descriptive statistics were used to determine global patterns behind this risk of children being orphaned. Linear regression models were fitted to determine factors associated with this risk, and the association with vaccination coverage was calculated. We found that there is tremendous global variation in the risk that COVID-19 deaths will lead to orphaned children, and that this risk is higher in countries below median GDP per capita (1·56 orphans per deaths) compared to countries above (0·09 orphans per death). Poverty prevalence (B = 2·32, p<0·01), GDP per capita (B = -0·23, p<0·05), and a greater proportion of people with NCDs being reproductive aged (B = 1·46, p<0·0001) were associated with this risk. There was a negative correlation between 2nd dose vaccination coverage and orphans per death (p<0·05). The risk of children being orphaned per COVID-19 death, alongside fertility rate, is due to there being a greater share of COVID-19 deaths among younger persons. This is more likely in poorer countries and those where the age distribution for non-communicable diseases that elevate COVID-19 mortality risk are more uniform. Due to vaccine coverage inequity, more children will suffer the loss of their parents in poorer countries.